INSTITUTIONAL WEAKNESS IN PERU: DOES THE LACK OF POLITICAL COMPETITION LIMITS THE CAPACITY BUILDING? - Rodríguez Cairo, Vladimir (2011)
At present there is a consensus in recognizing the importance of institutions, rules of society: formal and informal-to explain both success and failure of countries seeking development. In this perspective, Peru has not reached the longed-economic development because there is a weak institutional framework and does not effectively protect individual rights. The institutional framework has led throughout our history, the establishment of forms of government, populist and authoritarian. Our judicial system is not working properly: the judicial processes are inefficient (high cost and slow processes), there is political influence, court decisions are uncertain, there is widespread corruption, and access to justice is uneven. As a result of these characteristics, the legal system promotes legal uncertainty. In addition to the above, do not have a strong political party system. The institutional weakness affects our economic performance because business investment is affected and on the other hand, property rights are unclear or inconsistent, so we need to strengthen our institutional framework, especially the existence of institutions that ensure property rights and legal mechanisms to protect them. It is not simply to make laws, it is necessary to ensure compliance with them. Below is the history of institutionalism, the theoretical and conceptual framework of institutions and organizations as well as a brief analysis of the institutional weaknesses and capacity building, concluding with the most important ideas.